Pancasila dan Perdagangan di Era Globalisasi: PkM di PKBM Bhakti Asih, Ciledug, Kota Tangerang - Iman Lubis; Syamruddin Syamruddin; Andi Sopandi; Sri Sukapti; Fathur Rahman (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
This Community Service (CS) aims to reduce understanding of Pancasila in the era of globalization when the economy makes goods, services and culture freely flow between countries. The method used is lecture and question and answer discussion. The tool used is google meet. The meeting was conducted boldly. The implementation is carried out in four stages, namely survey, pre-activity, implementation, and PKM report. The target achievement in this CS is that participants can recall about Pancasila so that their behavior can reflect Pancasila. The discussion implemented in PKBM Bhakti Asih is the material of Pancasila and its origins, the dimensions of the globalization era of marketing, human resources, and finance and international trade.